ATTENDANCE and CO-OCCURRENCE of BIRDS FOLLOWING ARMY ANTS IN THE ATLANTIC RAIN FOREST - Pizo, Marco Aurelio [UNESP]; Melo, Adriano S. (Cooper Ornithological Soc, 2010)
In a first attempt to formally test competitive interactions among army-ant-following birds, we explored the patterns of occurrence of birds following swarms of army ants in the Atlantic rain forest of southeastern Brazil. We contrasted the frequency of occurrence of birds at ant swarms at a lowland and a highland site. Additionally, we assessed the patterns of co-occurrence of bird species at ant swarms, using null models to test for the possibility of competitive exclusion. Despite the larger number of attending bird species at the highland site, we detected no differences between the sites in either the frequency of attendance or the number of bird species per swarm. Analyses of co-occurrence did not reveal evidence of negative association of bird species attending ant swarms at the lowland site but did at the more species-rich highland site. Pairwise analyses showed that this negative association invariably involved two of the species attending ant swarms most frequently, Pyriglena leucoptera and Trichothraupis melanops, suggesting a competitive interaction. Possibly, although birds that are more dependent upon army ants avoid competitive exclusion by spatial segregation at the swarm's front, birds that follow army ants less frequently are occasionally excluded from the swarms.
Keywords: army ants; Atlantic forest; Brazil; competitive interactions; null models; Pyriglena leucoptera; Trichothraupis melanops